Effectiveness of combination therapy with ISA101 vaccine for the treatment of human papillomavirus-induced cervical cancer - Ding, Haigang; Zhang, Juan; Zhang, Feng; Xu, Yan; Yu, Yijun; Liang, Wenqing; Li, Qingping (Frontiers in Oncology, 2022)
Cervical cancer is one of the women-associated tumors that affects numerous people yearly. It is the fourth most common malignancy in women worldwide. Following early diagnosis, this cancer can be cured mainly by traditional methods such as surgery, tumor resection, and chemotherapy; nonetheless, it becomes more challenging to treat in advanced and metastatic stages. With the advent of novel treatments such as angiogenesis inhibitors or immuno-checkpoint blockers in recent years, the survival rate of patients with advanced cervical cancer has significantly increased. However, it has not yet reached a satisfactory level. It has been revealed that human papillomavirus (HPV) infection is responsible for more than 90% of cervical cancer cases. However, evidence revealed that monotherapy with anti-HPV vaccines such as ISA101 could not affect tumor growth and progression in patients with HPV-induced cervical cancer. Therefore, combining ISA101 and immune checkpoint blockers or other immunotherapeutic approaches may be more robust and effective than monotherapy with ISA101 or immune checkpoint blockers for treating cervical cancer. This review summarizes the ISA101 properties, advantages and disadvantages. Furthermore, various conducted combination therapies with ISA101 and the effectiveness and challenges of this treatment have been discussed.